2022
DOI: 10.1007/s10633-022-09880-0
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral optic neuritis after vaccination against the coronavirus disease: two case reports

Abstract: Background Due to the emergence of COVID-19, many countries have started mass immunization programs. To date, no cases of optic neuritis following COVID-19 vaccination have been reported in the literature. Case presentation Objective: Here, we report 2 cases of unilateral optic neuritis after vaccination against COVID-19 using the Sinopharm vaccine (Sinopharm Group Co. Ltd, China). Design The clinical history, examination, and test findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Other studies have reported similar neuro-ophthalmologic complications following other COVID-19 vaccines Ad26.COV2.S vaccine (Janssen Pharmaceutical Companies) [6], Pfizer-BioNTech vaccine, AstraZeneca-Oxford vaccine [7], Covishield vaccine [8], and Sinopharm vaccine [9]. Similar neuroophthalmologic complications have been reported following the administration of the measles vaccine [10,11].…”
Section: Discussionmentioning
confidence: 58%
“…Other studies have reported similar neuro-ophthalmologic complications following other COVID-19 vaccines Ad26.COV2.S vaccine (Janssen Pharmaceutical Companies) [6], Pfizer-BioNTech vaccine, AstraZeneca-Oxford vaccine [7], Covishield vaccine [8], and Sinopharm vaccine [9]. Similar neuroophthalmologic complications have been reported following the administration of the measles vaccine [10,11].…”
Section: Discussionmentioning
confidence: 58%
“…There have also been several case reports that suggest an increased risk of optic neuritis after COVID-19 vaccination 11 , 12 , 27 . A more recent database study indicated that the risk of optic neuritis following COVID-19 vaccination was low 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have reported that COVID-19 vaccination may increase the risk of systemic adverse events such as myocarditis, lymphadenopathy, and appendicitis 4 , 5 . The vaccines may also increase the risk of ocular adverse events such as uveitis 2 , 4 , 6 , 7 , 8 , scleritis 9 , retinal vein occlusion (RVO) 10 and optic neuritis 11 , 12 . However, because nearly all of these were case reports or case series, the association between vaccination and ocular adverse events has not been established.…”
mentioning
confidence: 99%
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple sclerosis (MS) or neuromyelitis optica spectrum disorders (NMOSD) after COVID-19 vaccination have been reported [ 1 , 2 , 3 , 4 , 5 , 6 ], while a complication of optic neuritis (ON) is also known [ 7 , 8 , 9 , 10 ]. Although idiopathic ON after COVID-19 vaccination is also reported [ 11 , 12 , 13 , 14 , 15 ], those visual prognoses are generally favorable. We report a case of atypical unilateral ON after receiving the BNT162b2 mRNA-based COVID-19 vaccine, in which the recovery of visual functions was restricted despite corticosteroid therapy.…”
Section: Introductionmentioning
confidence: 99%